Flowability properties of Labisia pumila herbal powder - Etti, Christopher Joseph; Yusof, Yus Aniza; Chin, Nyuk Ling; Mohd Tahir, Suraya (Elsevier, 2014)
This paper investigates the flowability properties of Labisia pumila (L. pumila) powder. Material properties of the powder and their influence on flowability were discussed. L. pumila, a popular Malaysian herb with therapeutic and medicinal functions was compressed into tablets using a stainless steel cylindrical uniaxial die with 13 mm diameter and compaction pressures of 7 to 25 MPa. Two feed weights, 0.5 and 0.7 g were used to form tablets. Compaction strength and density increased as compaction pressure increased resulting in tablets porosity reduction. Cohesion index, flow stability and caking strength were also determined to enhance the understanding of flowability properties of the L. pumila powder.